Shoe material and preparation method thereof
By modifying white carbon black and carbon fiber, combining natural rubber, butyl rubber and polystyrene-butadiene rubber, high-performance shoe materials are prepared, which solves the problem of insufficient performance of existing sole materials and achieves wear resistance, anti-slip and resistance Multiple performance improvements such as tearing and reduce production costs.
Patent Information
- Application Number
- CN202510033145.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of shoe materials, and particularly relates to a shoe material and a preparation method thereof. Background Art
[0002] Shoes are an indispensable daily necessity in people's lives. With the development of social economy, the continuous improvement of people's living standards and the continuous development of shoe materials, people's requirements for the functionality of shoe materials are also constantly increasing, especially the functional requirements for soles are getting higher and higher. For example, from the initial pursuit of protection and warmth, people are now beginning to pursue high-performance shoes with wear resistance, tear resistance, moisture resistance, non-slipness, comfort, lightness and environmental protection.
[0003] At present, the existing sole materials on the market mainly include leather, plastic, synthetic rubber and thermoplastic elastomer etc. Since most of the leather sole materials on the market are animal leather, they are not only expensive and unfavorable for ecological protection, but also the soles of leather materials are not water-resistant, and are easily deformed or rotten after being soaked in water, greatly shortening the service life of the shoes; although plastic is cheap and easy to obtain, when it is used as a sole material, the performances such as anti-skid and moisture-proof, wear resistance and comfort of the sole are relatively poor; thermoplastic elastomer has certain advantages in terms of wear resistance, weather resistance, tear resistance, comfort and environmental protection as a sole material, but its performance in terms of heat resistance, resilience, durability, etc. is relatively poor, and since thermoplastic elastomer is a relatively soft material, the surface friction is large, and it often sticks to the mold, the softer the product is, the easier it is to stick to the mold, and the requirements for the production mold are relatively high, and the price of thermoplastic elastomer is also relatively high, which is not suitable for large-scale production. Synthetic rubber as a sole material is not only low in price and simple in production process, but also has excellent properties such as wear resistance, anti-slip and moisture resistance, tear resistance, and elasticity. Therefore, soles with synthetic rubber as the main material have good development prospects in the current market.
[0004] The Chinese patent with publication number CN115368649A discloses an anti-skid rubber sole and its preparation method, which includes the following processes: mixing natural rubber, cis-1,4-butadiene rubber, chlorobutyl rubber, and chlorosulfonated polyethylene rubber; adding calcium carbonate, zinc oxide, zinc stearate, plasticizer dioctyl phthalate, sulfur, accelerator DM, and antioxidant RD, and mixing; plate vulcanization to obtain the rubber sole. The invention improves the weather resistance and processing performance of the rubber sole by compounding natural rubber and cis-1,4-butadiene rubber, and adding chlorobutyl rubber and chlorosulfonated polyethylene rubber to obtain higher tear strength and tensile strength; the interaction force between rubber molecular chains improves the anti-slip performance of the rubber sole; the free volume of the cis-1,4-butadiene rubber molecular chain is reduced, the loss factor of the rubber sole is increased, and the wear resistance is improved, thereby improving the comprehensive performance of the rubber shoe material. The Chinese patent with the publication number CN110317375A discloses an ice surface oil-resistant non-slip shoe material and its preparation method, wherein the raw materials include butyl rubber, butadiene rubber, nitrile rubber, solution-polymerized styrene butadiene rubber, white smoke, zinc oxide, antioxidant, plasticizer, silane coupling agent and vulcanization accelerator; the shoe material prepared by this formula is integrally formed with a specific pattern of the outsole or pasted on the outsole, and the obtained outsole has the advantages of oil resistance and non-slip, good mechanical properties and no fogging, excellent anti-slip performance, and can be suitable for use on ice and snow ground. However, the interface bonding strength and compatibility between the rubber base material and the filler in the shoe material in the above-mentioned prior art need to be further improved, thereby affecting the wear resistance, anti-slip and moisture resistance, tear resistance, corrosion resistance, aging resistance, elasticity and mechanical strength of the shoe sole. Therefore, it is a technical problem to be solved urgently to study a rubber shoe material with excellent properties such as wear resistance, anti-slip and moisture resistance, tear resistance, corrosion resistance, aging resistance and elasticity. Summary of the invention
[0005] In order to solve the deficiencies in the prior art, the purpose of the present invention is to provide a shoe material and a preparation method thereof. The present invention improves the compatibility and bonding strength between the filler white carbon black and the carbon fiber and the rubber base material by modifying the filler white carbon black and the carbon fiber, thereby significantly improving the mechanical properties, tear resistance, wear resistance, anti-slip performance, aging resistance, corrosion resistance and elasticity of the shoe material.
[0006] In order to achieve the above object, the present invention adopts the following technical solution: A shoe material comprises the following raw materials in parts by weight: 15-25 parts of natural rubber, 30-45 parts of butadiene rubber, 18-24 parts of solution-polymerized styrene-butadiene rubber, 8-15 parts of modified inorganic filler, 5-8 parts of lubricant, 5-10 parts of antioxidant, 2-5 parts of plasticizer, 3.5-6 parts of vulcanization accelerator, 2-4 parts of antioxidant and 15-25 parts of modified carbon fiber.
[0007] Furthermore, the modified inorganic filler is modified white carbon black, and the preparation method of the modified white carbon black is as follows: (1) Dry the ground white carbon black in a vacuum drying oven at 140-150°C for 10-12 hours to obtain high-temperature activated white carbon black for later use; (2) adding the high temperature activated silica obtained in step (1) to the epichlorohydrin solvent, stirring and mixing evenly, then adding γ-aminopropyltrimethoxysilane, and ultrasonically dispersing at 120-150° C. for 2-4 hours to obtain γ-aminopropyltrimethoxysilane-grafted silica for standby use; wherein the mass ratio of silica to γ-aminopropyltrimethoxysilane is 1:(35-40); (3) dispersing molybdenum disulfide powder in water, adding dithiocarbyl alcohol thereto, and subjecting to ultrasonic reaction for 8-12 hours to obtain hydroxylated molybdenum disulfide for later use; wherein the mass ratio of molybdenum disulfide powder, water and dithiocarbyl alcohol is (0.45-0.6):(150-300):(2.5-8); (4) adding the γ-aminopropyltrimethoxysilane grafted silica obtained in step (2) to the hydroxylated molybdenum disulfide obtained in step (3), stirring at a speed of 800-900 r / min for 2-4 hours, filtering, washing, and drying to obtain modified silica; wherein the molar ratio of the γ-aminopropyltrimethoxysilane grafted silica to the hydroxylated molybdenum disulfide is (0.12-0.16):(0.03-0.05).
[0008] Specifically, since the surface of silica contains a large number of hydroxyl groups, silica can easily form large agglomerates in the rubber base material, resulting in poor interfacial bonding strength and compatibility between the filler silica and the rubber base material, which adversely affects the performance of the rubber base material, and further affects the performance of the shoe material; therefore, the present application needs to modify the filler silica to improve the interfacial bonding strength and compatibility between silica and the rubber base material, and improve the comprehensive performance of the shoe material. The present application obtains silica grafted with γ-aminopropyltrimethoxysilane by grafting high-temperature activated silica with a coupling agent γ-aminopropyltrimethoxysilane, and then uses γ-aminopropyltrimethoxysilane to graft hydroxylated molybdenum disulfide onto silica to obtain modified silica. The methoxy group in γ-aminopropyltrimethoxysilane undergoes dehydration and condensation reaction with the silanol group on the surface of silica, reducing the hydroxyl group on the surface of silica and reducing the agglomerates of silica in the rubber base material, thereby increasing the interface bonding strength and compatibility between silica and the rubber base material, and improving the wear resistance and tear resistance of the shoe material; and the amino group in γ-aminopropyltrimethoxysilane can also react with the carboxyl group on the rubber molecular chain to form an amide bond, which increases the bonding strength between the silica filler and the rubber base material through chemical reaction, thereby improving the wear resistance, aging resistance and mechanical strength of the shoe material. At the same time, the introduction of amide bonds can also improve the corrosion resistance and mechanical strength of the shoe material; due to the introduction of molybdenum disulfide on the modified silica, The disulfide bonds contained in molybdenum disulfide can undergo coupling reaction with the rubber base material to form a cross-linked structure between rubber molecules, further increasing the interface bonding strength between the filler white carbon black and the rubber base material, thereby improving the strength, wear resistance and aging resistance of the rubber, and further improving the mechanical strength, wear resistance and aging resistance of the shoe material; at the same time, molybdenum disulfide can promote the vulcanization reaction of the rubber base material during the preparation of the shoe material, and as a strong oxidant, molybdenum disulfide can also react with the rubber vulcanizer to generate active intermediates, promote the vulcanization reaction of the rubber, significantly accelerate the vulcanization speed of the rubber and improve the vulcanization efficiency, and by accelerating the vulcanization reaction of the rubber, more sulfur bonds are formed in the rubber base material, thereby improving the strength, wear resistance and aging resistance of the rubber, and further improving the strength, wear resistance and aging resistance of the shoe material, and extending the service life of the shoe material; the modified white carbon black has high polarity while improving the compatibility and interface bonding strength with the rubber base material, thereby effectively improving the anti-slip performance of the manufactured shoe material.
[0009] Furthermore, the preparation method of the modified carbon fiber specifically comprises the following steps: 1) Add the carbon fiber to a mixed acid solution of concentrated sulfuric acid and concentrated nitric acid, mix and react for 4-6 hours in an oil bath at 75-80°C, cool, rinse and dry the reaction product to obtain the pretreated carbon fiber for later use; 2) adding the pretreated carbon fiber obtained in step 1) to an ethanol solution of 3-fluoropropyltriethoxysilane, subjecting the mixture to ultrasonic oscillation, filtering and washing the reaction product to obtain carbon fiber grafted with 3-fluoropropyltriethoxysilane for standby use; the temperature of the ultrasonic oscillation is 50-60° C., the ultrasonic oscillation time is 8-10 h, and the ultrasonic oscillation power is 80-100 W; the mass percentage of 3-fluoropropyltriethoxysilane in the ethanol solution of 3-fluoropropyltriethoxysilane is 3-6%; the dosage ratio of the pretreated carbon fiber to the ethanol solution of 3-fluoropropyltriethoxysilane is 1 g:50-200 mL; 3) Under nitrogen protection, mix polyethylene glycol and terminal hydroxyl polydimethylsiloxane, and then raise the temperature. The method comprises the following steps: heating the mixture to 150-160° C., heating the mixture until the mixture is completely melted, adding hexamethylene diisocyanate after the mixture is melted, and stirring the mixture for reaction for 3-5 hours to obtain a polyethylene glycol-polydimethylsiloxane block type long chain hyperbranched copolymer for standby use; the mass ratio of the polyethylene glycol, the terminal hydroxyl polydimethylsiloxane and the hexamethylene diisocyanate is 1:(0.5-0.7):(1.5-1.8); the molecular weight of the polyethylene glycol is 1000-1200; the viscosity of the terminal hydroxyl polydimethylsiloxane is 800-1000 mm 2 / s; 4) adding the 3-fluoropropyltriethoxysilane grafted carbon fiber obtained in step 2) to the polyethylene glycol-polydimethylsiloxane block type long chain hyperbranched copolymer obtained in step 3), stirring the reaction at a speed of 400-600 r / min for 5-7 hours, and after the reaction, centrifuging, washing and drying the reaction product to obtain modified carbon fiber; the mass ratio of the 3-fluoropropyltriethoxysilane grafted carbon fiber to the polyethylene glycol-polydimethylsiloxane block type long chain hyperbranched copolymer is 1:(1.8-2.2).
[0010] Specifically, carbon fiber is a high-strength, high-modulus material with excellent physical and chemical properties, such as high temperature resistance, friction resistance, corrosion resistance, etc. Carbon fiber, as a filler for rubber shoe materials, can enhance the wear resistance, tensile strength and tear resistance of rubber shoe materials, thereby improving the service life and performance of rubber shoe materials. However, due to the small number of active groups on the surface of carbon fiber, its compatibility with the rubber base material is poor, which makes the rubber shoe material easy to crack during the preparation process, thereby reducing the comprehensive performance of rubber shoe materials such as wear resistance, anti-slip and moisture resistance, tear resistance, corrosion resistance, and aging resistance, greatly shortening the service life of rubber shoe materials. Therefore, it is necessary to modify the carbon fiber to enhance its compatibility and interfacial bonding with the rubber base material.The present application firstly pre-treats the carbon fiber with a mixed acid solution of concentrated sulfuric acid and concentrated nitric acid to obtain pre-treated carbon fiber, thereby increasing the surface roughness of the carbon fiber and introducing a large number of active sites on its surface, which is beneficial to the subsequent grafting reaction; then, the carbon fiber is grafted with a 3-fluoropropyltriethoxysilane ethanol solution, wherein the siloxane in the 3-fluoropropyltriethoxysilane ethanol solution is hydrolyzed to generate Si-OH, which undergoes dehydration condensation with the hydroxyl groups on the surface of the carbon fiber, thereby introducing fluoropropyl groups, halogen atoms, and alkyl chains onto the surface of the carbon fiber, which not only improves the compatibility between the carbon fiber and the rubber base material, but also the introduced fluoropropyl groups can To improve the hydrophobicity of the rubber base material, thereby improving the anti-wet and anti-skid performance of the rubber shoe material. At the same time, due to the adhesion of the halogen atoms, the anti-wet and anti-skid performance of the rubber shoe material can also be improved; finally, 3-fluoropropyltriethoxysilane will be hydrolyzed to generate silanol, and the silanol contained in the polyethylene glycol-polydimethylsiloxane block type long-chain hyperbranched copolymer can react with it to form a covalent bond, so that the polyethylene glycol-polydimethylsiloxane block type long-chain hyperbranched copolymer is grafted on the surface of the carbon fiber to obtain a modified carbon fiber. The modified carbon fiber has a The silicon-oxygen segments contained in the polymer are chemically stable and have excellent aging and corrosion resistance. During the vulcanization process of the rubber base material, the performance of the rubber base material is significantly affected. Through the protection of the silicon-oxygen segments, the performance of the modified carbon fiber is not weakened, but can improve the aging, corrosion and wear resistance of the rubber base material, thereby improving the wear resistance, corrosion resistance and aging resistance of the rubber shoe material and extending the service life of the rubber shoe material; and the polyethylene glycol-polydimethylsiloxane block type long-chain hyperbranched copolymer has a highly branched topological structure, which makes it have a small fluid mechanics volume, low viscosity, and contains a large number of terminal functional Therefore, the modified carbon fiber grafted with polyethylene glycol-polydimethylsiloxane block type long-chain hyperbranched copolymer can be well connected with other compounds in the rubber base material, which not only increases the compatibility and interfacial bonding force between the carbon fiber and the rubber base material, but also increases the flexibility of the molecular chain of the rubber material and the free space of the rubber material when it is loaded, thereby improving the elasticity of the rubber shoe material. At the same time, the polyethylene glycol-polydimethylsiloxane block type long-chain hyperbranched copolymer has a highly branched topological structure and can also increase the chain entanglement between rubber molecules, thereby improving the mechanical strength of the rubber shoe material.
[0011] Furthermore, the lubricant is any one or more of stearic acid, graphite and calcium carbonate.
[0012] Furthermore, the antioxidant is any one or more of antioxidant 1010, antioxidant 264 and antioxidant TNP.
[0013] Furthermore, the plasticizer is any one or more of methyl stearate, dioctyl phthalate and stearamide.
[0014] Furthermore, the vulcanization accelerator is any one or more of 4,4-dithiodimorpholine and 2-benzothiazolyl-N-morpholinyl sulfide.
[0015] Furthermore, the antioxidant is any one or more of antioxidant RD, antioxidant MB, antioxidant 4010, antioxidant 4010NA, and antioxidant 4020.
[0016] Furthermore, a method for preparing the above-mentioned shoe material comprises the following steps: Step S1, mixing and stirring the lubricant, antioxidant and vulcanization accelerator to obtain a compounding agent for standby use; Step S2, mixing natural rubber, cis-1,4-butadiene rubber and solution polystyrene-butadiene rubber into an internal mixer for the first internal mixing, then adding part of the modified inorganic filler and continuing the second internal mixing, and when the temperature reaches 115-120° C., the rubber masterbatch is taken out from the internal mixer for standby use; Step S3, placing the rubber masterbatch obtained in step S2, the modified carbon fiber, the compounding agent obtained in step S1, the antioxidant, the plasticizer and the remaining modified inorganic filler into a rubber mixer for uniform mixing to obtain a mixed rubber for standby use; Step S4, placing the mixed rubber obtained in step S3 on a double-roll open mill for mixing for several times, adjusting the distance between the rollers to a desired thickness to obtain a film for standby use; Step S5, punching out shoe pieces of different shapes from the film obtained in step S4, wherein the shapes of the shoe pieces are designed according to different sole patterns, and the shoe pieces are placed in a matching mold for vulcanization to obtain the shoe material.
[0017] Furthermore, in step S2, the first mixing time is 8-15 minutes; the second mixing time is 6-8 minutes; the number of mixing in step S4 is 20-25 times; and the vulcanization temperature of the shoe piece in the mold in step S5 is 150-160°C.
[0018] Compared with the prior art, the present invention has the following positive and beneficial effects: (1) The present invention obtains γ-aminopropyltrimethoxysilane-grafted silica by subjecting high-temperature activated silica to a grafting reaction with a coupling agent γ-aminopropyltrimethoxysilane, and then uses γ-aminopropyltrimethoxysilane to graft hydroxylated molybdenum disulfide onto the silica to obtain modified silica. The methoxy group in γ-aminopropyltrimethoxysilane undergoes dehydration and condensation reaction with the silanol group on the surface of silica, reducing the hydroxyl group on the surface of silica and reducing the agglomerates of silica in the rubber base material, thereby increasing the interface bonding strength and compatibility between silica and the rubber base material, and improving the wear resistance and tear resistance of the shoe material; and the amino group in γ-aminopropyltrimethoxysilane can also react with the carboxyl group on the rubber molecular chain to form an amide bond, which increases the bonding strength between the silica filler and the rubber base material through chemical reaction, thereby improving the wear resistance, aging resistance and mechanical strength of the shoe material. At the same time, the introduction of the amide bond can also improve the corrosion resistance and mechanical strength of the shoe material; since molybdenum disulfide is introduced into the modified silica, the disulfide bonds contained in the molybdenum disulfide can undergo coupling reaction with the rubber base material to form a cross-linked structure between the rubber molecules, further The first step increases the interface bonding strength between the filler white carbon black and the rubber base material, thereby improving the strength, wear resistance and aging resistance of the rubber, and further improving the mechanical strength, wear resistance and aging resistance of the shoe material; at the same time, molybdenum disulfide can promote the vulcanization reaction of the rubber base material in the process of shoe material preparation, and molybdenum disulfide, as a strong oxidant, can also react with the rubber vulcanizer to generate an active intermediate, promote the vulcanization reaction of the rubber, significantly accelerate the rubber vulcanization speed and improve the vulcanization efficiency, and accelerate the rubber vulcanization reaction to form more sulfur bonds in the rubber base material, thereby improving the strength, wear resistance and aging resistance of the rubber, and further improving the strength, wear resistance and aging resistance of the shoe material, and extending the service life of the shoe material; the modified white carbon black has high polarity while improving the compatibility and interface bonding strength with the rubber base material, thereby effectively improving the anti-slip performance of the manufactured shoe material.
[0019] (2) The present invention firstly pre-treats the carbon fiber with a mixed acid solution of concentrated sulfuric acid and concentrated nitric acid to obtain pre-treated carbon fiber, thereby increasing the surface roughness of the carbon fiber and introducing a large number of active sites on the surface, which is beneficial to the subsequent grafting reaction; then, the carbon fiber is grafted with 3-fluoropropyltriethoxysilane ethanol solution, wherein the siloxane in the ethanol solution of 3-fluoropropyltriethoxysilane is hydrolyzed to generate Si-OH, which undergoes dehydration condensation with the hydroxyl groups on the surface of the carbon fiber, thereby introducing fluoropropyl groups, halogen atoms, and alkyl chains onto the surface of the carbon fiber, which not only improves the compatibility between the carbon fiber and the rubber base material, but also improves the compatibility of the introduced fluoropropyl groups with the rubber base material. The base can improve the hydrophobicity of the rubber base material, thereby improving the anti-wet and anti-skid performance of the rubber shoe material. At the same time, due to the adhesion of the halogen atoms, the anti-wet and anti-skid performance of the rubber shoe material can also be improved; finally, 3-fluoropropyltriethoxysilane will be hydrolyzed to generate silanol, and the silanol contained in the polyethylene glycol-polydimethylsiloxane block type long-chain hyperbranched copolymer can react with it to form a covalent bond, so that the polyethylene glycol-polydimethylsiloxane block type long-chain hyperbranched copolymer is grafted on the surface of the carbon fiber to obtain a modified carbon fiber. The modified carbon fiber has a high molecular weight and a high molecular weight. The silicon-oxygen segments contained in the copolymer are chemically stable and have excellent aging and corrosion resistance. During the vulcanization process of the rubber base material, the performance of the rubber base material is significantly affected. Through the protection of the silicon-oxygen segments, the performance of the modified carbon fiber is not weakened, but can improve the aging, corrosion and wear resistance of the rubber base material, thereby improving the wear resistance, corrosion resistance and aging resistance of the rubber shoe material and extending the service life of the rubber shoe material; and the polyethylene glycol-polydimethylsiloxane block type long-chain hyperbranched copolymer has a highly branched topological structure, which makes it have a small fluid mechanics volume, low viscosity, and contains a large amount of terminal work. Therefore, the modified carbon fiber grafted with polyethylene glycol-polydimethylsiloxane block type long-chain hyperbranched copolymer can be well connected with other compounds in the rubber base material, which not only increases the compatibility and interfacial bonding force between the carbon fiber and the rubber base material, but also increases the flexibility of the molecular chain of the rubber material and the free space of the rubber material when it is loaded, thereby improving the elasticity of the rubber shoe material. At the same time, the polyethylene glycol-polydimethylsiloxane block type long-chain hyperbranched copolymer has a highly branched topological structure and can also increase the chain entanglement between rubber molecules, thereby improving the mechanical strength of the rubber shoe material.
[0020] (3) The present invention uses natural rubber, cis-1,4-butadiene rubber and solution polymerized styrene-butadiene rubber as the base materials of rubber shoe materials. Natural rubber has the characteristics of good tear resistance, high elasticity and excellent processing performance, but poor wear resistance; cis-1,4-butadiene rubber has the advantages of high elasticity, good wear resistance and good cold resistance, and low heat generation under dynamic load, good flexural resistance and dynamic performance; solution polymerized styrene-butadiene rubber has good wear resistance, heat resistance, wet skid resistance and aging resistance, and has good compatibility with natural rubber and cis-1,4-butadiene rubber. Blending the three can improve the tear resistance, wear resistance, wet skid resistance, aging resistance and elasticity of the rubber material, so that the rubber shoe material prepared therefrom has good wear resistance, anti-skid and moisture resistance, tear resistance, aging resistance and elasticity. DETAILED DESCRIPTION
[0021] The technical solution of the present application will be described clearly and completely in conjunction with the following embodiments. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0022] In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All reagents used without special instructions are conventional reagents used in the art, and all reagents or instruments used without specifying the manufacturer are conventional products that can be purchased commercially.
[0023] Example 1 A shoe material comprises the following raw materials in parts by weight: 15 parts of natural rubber, 30 parts of butadiene rubber, 18 parts of solution-polymerized styrene-butadiene rubber, 8 parts of modified white carbon black, 5 parts of lubricant stearic acid, 5 parts of antioxidant 1010, 2 parts of plasticizer methyl stearate, 3.5 parts of vulcanization accelerator 4,4-dithiodimorpholine, 2 parts of antioxidant RD and 15 parts of modified carbon fiber.
[0024] A method for preparing a shoe material comprises the following steps: Step S1, mixing and stirring the lubricant stearic acid, the antioxidant RD, and the vulcanization accelerator 4,4-dithiodimorpholine to obtain a compounding agent for standby use; Step S2, mixing natural rubber, cis-1,4-butadiene rubber and solution polystyrene-butadiene rubber into an internal mixer for the first internal mixing for 8 minutes, then adding modified silica accounting for 60% of the total mass of the modified silica and continuing the second internal mixing for 6 minutes, and when the temperature reaches 115° C., extracting the rubber masterbatch from the internal mixer for standby use; Step S3, placing the rubber masterbatch obtained in step S2, the modified carbon fiber, the compounding agent obtained in step S1, the antioxidant 1010, the plasticizer methyl stearate and the modified silica accounting for 40% of the total mass of the modified silica into a rubber mixer for uniform mixing to obtain a mixed rubber for standby use; Step S4, placing the mixed rubber obtained in step S3 on a double-roll open mill for mixing 20 times, adjusting the distance between the rollers to a desired thickness to obtain a film for standby use; Step S5, punching out shoe pieces of different shapes from the film obtained in step S4, wherein the shapes of the shoe pieces are designed according to different sole patterns, and the shoe pieces are placed in a matching mold for vulcanization. The vulcanization temperature of the shoe pieces in the mold is 150° C., thereby obtaining the shoe material of the present invention.
[0025] The preparation method of modified silica specifically comprises the following steps: (1) Dry the ground silica in a vacuum drying oven at 140°C for 12 hours to obtain high-temperature activated silica for later use; (2) adding the high temperature activated silica obtained in step (1) to the epichlorohydrin solvent, stirring and mixing evenly, then adding γ-aminopropyltrimethoxysilane, and ultrasonically dispersing at 120° C. for 4 h to obtain γ-aminopropyltrimethoxysilane-grafted silica for standby use; wherein the mass ratio of silica to γ-aminopropyltrimethoxysilane is 1:35; (3) dispersing molybdenum disulfide powder in water, adding dithiocarbyl alcohol thereto, and subjecting to ultrasonic reaction for 8 hours to obtain hydroxylated molybdenum disulfide for later use; wherein the mass ratio of molybdenum disulfide powder, water, and dithiocarbyl alcohol is 0.45:150:2.5; (4) Adding the hydroxylated molybdenum disulfide obtained in step (3) to the γ-aminopropyltrimethoxysilane-grafted silica obtained in step (2), stirring the mixture at a speed of 800 r / min for 4 h, filtering, washing, and drying to obtain modified silica; wherein the molar ratio of the γ-aminopropyltrimethoxysilane-grafted silica to the hydroxylated molybdenum disulfide is 0.12:0.03.
[0026] The preparation method of the modified carbon fiber specifically comprises the following steps: 1) Add the carbon fiber to a mixed acid solution of concentrated sulfuric acid and concentrated nitric acid, mix and react for 6 hours in an oil bath at 75°C, cool, rinse and dry the reaction product to obtain the pretreated carbon fiber for later use; 2) adding the pretreated carbon fiber obtained in step 1) to an ethanol solution of 3-fluoropropyltriethoxysilane, subjecting the reaction product to ultrasonic oscillation, filtering and washing the reaction product to obtain carbon fiber grafted with 3-fluoropropyltriethoxysilane for standby use; the temperature of the ultrasonic oscillation is 50° C., the ultrasonic oscillation time is 10 h, and the power of the ultrasonic oscillation is 80 W; the mass percentage of 3-fluoropropyltriethoxysilane in the ethanol solution of 3-fluoropropyltriethoxysilane is 3%; the amount ratio of the pretreated carbon fiber to the ethanol solution of 3-fluoropropyltriethoxysilane is 1 g:50 mL; 3) Under nitrogen protection, mix polyethylene glycol and terminal hydroxyl polydimethylsiloxane, and then raise the temperature. The mixture is heated to 150°C until completely melted, and after melting, hexamethylene diisocyanate is added, and the mixture is stirred for reaction for 5 hours to obtain a polyethylene glycol-polydimethylsiloxane block type long-chain hyperbranched copolymer for standby use; the mass ratio of the polyethylene glycol, the terminal hydroxyl polydimethylsiloxane and the hexamethylene diisocyanate is 1:0.5:1.5; the molecular weight of the polyethylene glycol is 1000; the viscosity of the terminal hydroxyl polydimethylsiloxane is 800 mm 2 / s; 4) adding the 3-fluoropropyltriethoxysilane grafted carbon fiber obtained in step 2) to the polyethylene glycol-polydimethylsiloxane block type long-chain hyperbranched copolymer obtained in step 3), stirring the reaction at a speed of 400 r / min for 7 hours, and after the reaction, centrifuging, washing, and drying the reaction product to obtain modified carbon fiber; the mass ratio of the 3-fluoropropyltriethoxysilane grafted carbon fiber to the polyethylene glycol-polydimethylsiloxane block type long-chain hyperbranched copolymer is 1:1.8.
[0027] Example 2 A shoe material comprises the following raw materials in parts by weight: 20 parts of natural rubber, 40 parts of butadiene rubber, 21 parts of solution-polymerized styrene-butadiene rubber, 12 parts of modified white carbon black, 6 parts of lubricant calcium carbonate, 8 parts of antioxidant 264, 4 parts of plasticizer dioctyl phthalate, 5 parts of vulcanization accelerator 2-benzothiazolyl-N-morpholinyl sulfide, 3 parts of antioxidant MB and 20 parts of modified carbon fiber.
[0028] A method for preparing a shoe material comprises the following steps: Step S1, mixing and stirring the lubricant calcium carbonate, the antioxidant MB, and the vulcanization accelerator 2-benzothiazolyl-N-morpholinyl sulfide to obtain a compounding agent for standby use; Step S2, mixing natural rubber, cis-1,4-butadiene rubber and solution polymerized styrene-butadiene rubber into an internal mixer for the first internal mixing for 12 minutes, then adding modified silica accounting for 60% of the total mass of the modified silica and continuing the second internal mixing for 7 minutes, and when the temperature reaches 118° C., extracting the rubber masterbatch from the internal mixer for standby use; Step S3, placing the rubber masterbatch obtained in step S2, the modified carbon fiber, the compounding agent obtained in step S1, the antioxidant 264, the plasticizer dioctyl phthalate and the modified silica accounting for 40% of the total mass of the modified silica into a rubber mixer for uniform mixing to obtain a mixed rubber for standby use; Step S4, placing the mixed rubber obtained in step S3 on a double-roll open mill for mixing 23 times, adjusting the distance between the rolls to a desired thickness to obtain a film for standby use; Step S5, punching out shoe pieces of different shapes from the film obtained in step S4, wherein the shapes of the shoe pieces are designed according to different sole patterns, and placing the shoe pieces in a matching mold for vulcanization. The vulcanization temperature of the shoe pieces in the mold is 155° C., thereby obtaining the shoe material of the present invention.
[0029] The preparation method of modified silica specifically comprises the following steps: (1) Dry the ground silica in a vacuum drying oven at 145°C for 11 hours to obtain high-temperature activated silica for later use; (2) adding the high temperature activated silica obtained in step (1) to the epichlorohydrin solvent, stirring and mixing evenly, then adding γ-aminopropyltrimethoxysilane, and ultrasonically dispersing at 135° C. for 3 h to obtain γ-aminopropyltrimethoxysilane-grafted silica for standby use; wherein the mass ratio of silica to γ-aminopropyltrimethoxysilane is 1:38; (3) dispersing molybdenum disulfide powder in water, adding dithiocarbyl alcohol thereto, and subjecting to ultrasonic reaction for 10 hours to obtain hydroxylated molybdenum disulfide for later use; wherein the mass ratio of molybdenum disulfide powder, water, and dithiocarbyl alcohol is 0.5:240:6; (4) Adding the hydroxylated molybdenum disulfide obtained in step (3) to the γ-aminopropyltrimethoxysilane-grafted silica obtained in step (2), stirring at a speed of 850 r / min for 3 hours, filtering, washing, and drying to obtain modified silica. The molar ratio of the γ-aminopropyltrimethoxysilane-grafted silica to the hydroxylated molybdenum disulfide is 0.15:0.04.
[0030] The preparation method of the modified carbon fiber specifically comprises the following steps: 1) Add the carbon fiber to a mixed acid solution of concentrated sulfuric acid and concentrated nitric acid, mix and react for 5 hours in an oil bath at 78°C, cool, rinse and dry the reaction product to obtain the pretreated carbon fiber for later use; 2) adding the pretreated carbon fiber obtained in step 1) to an ethanol solution of 3-fluoropropyltriethoxysilane, subjecting the reaction product to ultrasonic oscillation, filtering and washing the reaction product to obtain carbon fiber grafted with 3-fluoropropyltriethoxysilane for standby use; the temperature of the ultrasonic oscillation is 55° C., the ultrasonic oscillation time is 9 h, and the ultrasonic oscillation power is 90 W; the mass percentage of 3-fluoropropyltriethoxysilane in the ethanol solution of 3-fluoropropyltriethoxysilane is 4.5%; the amount ratio of the pretreated carbon fiber to the ethanol solution of 3-fluoropropyltriethoxysilane is 1 g:120 mL; 3) Under nitrogen protection, mix polyethylene glycol and terminal hydroxyl polydimethylsiloxane, and then raise the temperature. The mixture is heated to 155°C until completely melted, and after melting, hexamethylene diisocyanate is added, and the mixture is stirred for reaction for 4 hours to obtain a polyethylene glycol-polydimethylsiloxane block type long-chain hyperbranched copolymer for standby use; the mass ratio of the polyethylene glycol, the terminal hydroxyl polydimethylsiloxane and the hexamethylene diisocyanate is 1:0.6:1.6; the molecular weight of the polyethylene glycol is 1100; the viscosity of the terminal hydroxyl polydimethylsiloxane is 900 mm 2 / s; 4) adding the 3-fluoropropyltriethoxysilane grafted carbon fiber obtained in step 2) to the polyethylene glycol-polydimethylsiloxane block type long-chain hyperbranched copolymer obtained in step 3), stirring the reaction at a speed of 500 r / min for 6 hours, and after the reaction, centrifuging, washing, and drying the reaction product to obtain modified carbon fiber; the mass ratio of the 3-fluoropropyltriethoxysilane grafted carbon fiber to the polyethylene glycol-polydimethylsiloxane block type long-chain hyperbranched copolymer is 1:2.
[0031] Example 3 A shoe material comprises the following raw materials in parts by weight: 25 parts of natural rubber, 45 parts of butadiene rubber, 24 parts of solution-polymerized styrene-butadiene rubber, 15 parts of modified white carbon black, 8 parts of lubricant graphite, 10 parts of antioxidant TNP, 5 parts of plasticizer stearamide, 6 parts of vulcanization accelerator 2-benzothiazolyl-N-morpholinyl sulfide, 4 parts of antioxidant 4010 and 25 parts of modified carbon fiber.
[0032] A method for preparing a shoe material comprises the following steps: Step S1, mixing and stirring lubricant graphite, antioxidant 4010, and vulcanization accelerator 2-benzothiazolyl-N-morpholinyl sulfide to obtain a compounding agent for standby use; Step S2, mixing natural rubber, cis-1,4-butadiene rubber and solution polymerized styrene-butadiene rubber into an internal mixer for the first internal mixing, the mixing time is 15 minutes, then adding modified silica accounting for 60% of the total mass of the modified silica and continuing the second internal mixing, the mixing time is 8 minutes, and when the temperature reaches 120° C., the rubber masterbatch is taken out from the internal mixer for standby use; Step S3, placing the rubber masterbatch obtained in step S2, the modified carbon fiber, the compounding agent obtained in step S1, the antioxidant TNP, the plasticizer stearamide and the modified silica accounting for 40% of the total mass of the modified silica into a rubber mixer for uniform mixing to obtain a mixed rubber for standby use; Step S4, placing the mixed rubber obtained in step S3 on a double-roll open mill for mixing 25 times, adjusting the roller spacing to a desired thickness to obtain a film for standby use; Step S5, punching out shoe pieces of different shapes from the film obtained in step S4, wherein the shapes of the shoe pieces are designed according to different sole patterns, and the shoe pieces are placed in a matching mold for vulcanization. The vulcanization temperature of the shoe pieces in the mold is 160° C., and the shoe material of the present invention is obtained.
[0033] The preparation method of modified silica specifically comprises the following steps: (1) Dry the ground silica in a vacuum drying oven at 150°C for 10 hours to obtain high-temperature activated silica for later use; (2) adding the high temperature activated silica obtained in step (1) into the epichlorohydrin solvent, stirring and mixing evenly, then adding γ-aminopropyltrimethoxysilane, and ultrasonically dispersing at 150° C. for 2 h to obtain γ-aminopropyltrimethoxysilane-grafted silica for later use; wherein the mass ratio of silica to γ-aminopropyltrimethoxysilane is 1:40; (3) dispersing molybdenum disulfide powder in water, adding dithiopropanol thereto, and subjecting to ultrasonic reaction for 12 hours to obtain hydroxylated molybdenum disulfide for later use; wherein the mass ratio of molybdenum disulfide powder, water, and dithiopropanol is 0.6:300:8; (4) Adding the hydroxylated molybdenum disulfide obtained in step (3) to the γ-aminopropyltrimethoxysilane-grafted silica obtained in step (2), stirring the mixture at a speed of 900 r / min for 2 h, filtering, washing, and drying to obtain modified silica. The molar ratio of the γ-aminopropyltrimethoxysilane-grafted silica to the hydroxylated molybdenum disulfide is 0.16:0.05.
[0034] The preparation method of the modified carbon fiber specifically comprises the following steps: 1) Add the carbon fiber to a mixed acid solution of concentrated sulfuric acid and concentrated nitric acid, mix and react for 4 hours in an oil bath at 80°C, cool, rinse and dry the reaction product to obtain the pretreated carbon fiber for later use; 2) adding the pretreated carbon fiber obtained in step 1) to an ethanol solution of 3-fluoropropyltriethoxysilane, ultrasonically oscillating, filtering and washing the reaction product to obtain 3-fluoropropyltriethoxysilane grafted carbon fiber for standby use; the temperature of the ultrasonic oscillation is 60° C., the ultrasonic oscillation time is 8 h, and the power of the ultrasonic oscillation is 100 W; the mass percentage of 3-fluoropropyltriethoxysilane in the ethanol solution of 3-fluoropropyltriethoxysilane is 6%; the amount ratio of the pretreated carbon fiber to the ethanol solution of 3-fluoropropyltriethoxysilane is 1 g:200 mL; 3) Under nitrogen protection, mix polyethylene glycol and terminal hydroxyl polydimethylsiloxane, and then raise the temperature. The mixture is heated to 160°C until completely melted, and after melting, hexamethylene diisocyanate is added, and the reaction is stirred for 3 hours to obtain a polyethylene glycol-polydimethylsiloxane block type long-chain hyperbranched copolymer for standby use; the mass ratio of the polyethylene glycol, the terminal hydroxyl polydimethylsiloxane and the hexamethylene diisocyanate is 1: 0.7: 1.8; the molecular weight of the polyethylene glycol is 1200; the viscosity of the terminal hydroxyl polydimethylsiloxane is 1000mm 2 / s; 4) adding the 3-fluoropropyltriethoxysilane grafted carbon fiber obtained in step 2) to the polyethylene glycol-polydimethylsiloxane block type long-chain hyperbranched copolymer obtained in step 3), stirring the mixture at a speed of 600 r / min for 5 hours, and after the reaction, centrifuging, washing, and drying the reaction product to obtain modified carbon fiber; the mass ratio of the 3-fluoropropyltriethoxysilane grafted carbon fiber to the polyethylene glycol-polydimethylsiloxane block type long-chain hyperbranched copolymer is 1: 2.2.
[0035] Comparative Example 1 In this comparative example, except that the modified silica in the shoe material raw material is replaced by an equal amount of ordinary unmodified silica, the other raw material components of the shoe material, the shoe material preparation method and the modified carbon fiber preparation method are exactly the same as those in Example 2.
[0036] Comparative Example 2 In this comparative example, except that the modified carbon fiber in the shoe material raw material is replaced by an equal amount of ordinary unmodified carbon fiber, the other raw material components of the shoe material, the shoe material preparation method and the preparation method of modified white carbon black are exactly the same as those in Example 2.
[0037] Comparative Example 3 In this comparative example, except that molybdenum disulfide is not added to the modified white carbon black, the other raw material components of the shoe material, the shoe material preparation method and the modified carbon fiber preparation method are exactly the same as those in Example 2.
[0038] Comparative Example 4 In this comparative example, except that no polyethylene glycol-polydimethylsiloxane block type long-chain hyperbranched copolymer is added to the modified carbon fiber, the other raw material components of the shoe material, the shoe material preparation method and the modified white carbon black preparation method are exactly the same as those in Example 2.
[0039] Comparative Example 5 In the preparation step 2) of the modified carbon fiber in this comparative example, the coupling agent 3-fluoropropyltriethoxysilane is replaced with an unequal amount of coupling agent γ-methacryloxypropyltrimethoxysilane. The other raw material components of the shoe material, the shoe material preparation method and the preparation method of modified white carbon black are exactly the same as those in Example 2.
[0040] Test example Performance test samples: The shoe materials prepared in Examples 1-3 and Comparative Examples 1-5 were injected into a sole mold of the same specification, and demolded after compression molding at 120° C. to obtain sole samples. The sole samples were taken for performance testing. The specific test results are shown in Tables 1 and 2.
[0041] Performance test items: Mechanical properties test: With GB / T 528-2009 and GB / T 529-2008 as reference standards, the tensile properties and tear properties of the sole samples were tested using an electronic tensile testing machine. The test results are shown in Table 1. The size of the sole samples is 100 mm × 5.0 mm × 2.0 mm, and the tensile rate is 500 mm / min. Wear scar length test: GB / T3903.2-2008 "General test method for wear resistance of footwear" is used as a reference standard to test the wear resistance of the sole samples. The test results are shown in Table 1. The smaller the wear scar length, the better the wear resistance of the sample. Test Anti-slip performance test: Using HG / T 3780-2005 as the reference standard, the dry / wet anti-slip performance of the sole samples was tested. The test results are shown in Table 1. Water was used as the wet medium. The sole samples were square and had a size of 76 mm × 76 mm. Corrosion resistance test: The sole samples were placed in a 50% by mass dilute hydrochloric acid solution and soaked for 600 hours to observe whether there were any changes in the sole samples. The test results are shown in Table 1. Aging resistance test: Take the sole sample and place it under a sunlight simulation lamp with a UV intensity of 500±4μW / cm 2 , under the condition of relative humidity of 2%, samples were taken at fixed points after exposure to simulated sunlight for 50h, 100h, 150h, 200h, and 250h. The change of color difference during UV exposure was tested by CR-10 colorimeter, and the corresponding data were recorded. The test results are shown in Table 2; Elasticity test: The elasticity of the sole sample was tested according to GB / T 7759.1-2015 "Determination of compression set of vulcanized rubber or thermoplastic rubber Part 1: At room temperature and elevated temperature". The test results are shown in Table 1, where the compression set rate is used to characterize the elasticity of the sole sample. The smaller the compression set rate, the better the elasticity of the sole sample.
[0042] Table 1 Performance test data of the sole samples prepared in Examples 1-3 and Comparative Examples 1-5 Table 2 Aging resistance test data of the sole samples prepared in Examples 1-3 and Comparative Examples 1-5 It can be seen from the data in Table 1 and Table 2 that the hard mechanical properties (tensile strength, tear strength), wear resistance, anti-skid performance, aging resistance, corrosion resistance and elasticity of the soles made of the shoe materials prepared in Examples 1-3 of the present application are better than those of Comparative Examples 1-5. This is mainly because the present application improves the compatibility and bonding strength between the filler white carbon black and carbon fiber and the rubber base material by modifying the filler white carbon black and carbon fiber, thereby significantly improving the mechanical properties (tensile strength, tear strength), wear resistance, anti-skid performance, aging resistance, corrosion resistance and elasticity of the shoe material. It can be seen from the comparison of Comparative Examples 1 and 3 with Example 2 that the present application obtains white carbon black grafted with γ-aminopropyltrimethoxysilane by grafting white carbon black after high temperature activation with coupling agent γ-aminopropyltrimethoxysilane, and then uses γ-aminopropyltrimethoxysilane to graft hydroxylated molybdenum disulfide onto white carbon black to obtain modified white carbon black. The methoxy group in γ-aminopropyltrimethoxysilane undergoes dehydration and condensation reaction with the silanol group on the surface of silica, reducing the hydroxyl group on the surface of silica and reducing the agglomerates of silica in the rubber base material, thereby increasing the interface bonding strength and compatibility between silica and the rubber base material, and improving the wear resistance and tear resistance of the shoe material; and the amino group in γ-aminopropyltrimethoxysilane can also react with the carboxyl group on the rubber molecular chain to form an amide bond, which increases the bonding strength between the silica filler and the rubber base material through chemical reaction, thereby improving the wear resistance, aging resistance and mechanical properties of the shoe material. At the same time, the introduction of amide bonds can also improve the corrosion resistance and mechanical strength of the shoe material; since molybdenum disulfide is introduced into the modified silica, the disulfide bonds contained in the molybdenum disulfide can undergo coupling reaction with the rubber base material to form a cross-linked structure between rubber molecules, further increasing the filler The interface bonding strength between white carbon black and rubber base material is improved, thereby improving the mechanical strength, wear resistance and aging resistance of rubber, and further improving the mechanical strength performance, wear resistance and aging resistance of shoe materials; at the same time, molybdenum disulfide can also promote the vulcanization reaction of rubber base material in the process of shoe material preparation, and molybdenum disulfide, as a strong oxidant, can also react with rubber vulcanizing agent to generate active intermediates, promote the vulcanization reaction of rubber, significantly accelerate the vulcanization speed of rubber and improve the vulcanization efficiency, and by accelerating the vulcanization reaction of rubber, more sulfur bonds are formed in the rubber base material, thereby improving the strength, wear resistance and aging resistance of rubber, and further improving the mechanical strength, tear resistance, wear resistance and aging resistance of shoe materials, and extending the service life of shoe materials; the modified white carbon black has high polarity while improving the compatibility and interface bonding strength with the rubber base material, thereby effectively improving the anti-slip performance of the manufactured shoe materials.It can be seen from the comparison of Comparative Examples 2, 4, and 5 with Example 2 that the present application uses 3-fluoropropyl triethoxysilane ethanol solution to graft the pretreated carbon fiber. The siloxane in the ethanol solution of 3-fluoropropyl triethoxysilane is hydrolyzed to generate Si-OH, which is dehydrated and condensed with the hydroxyl groups on the surface of the pretreated carbon fiber, and the fluoropropyl group, halogen atom fluorine and alkyl chain are introduced into the surface of the carbon fiber, which can not only improve the compatibility between the carbon fiber and the rubber base material, but also the introduced fluoropropyl group can improve the hydrophobicity of the rubber base material, thereby improving the anti-wet and anti-slip properties of the rubber shoe material. At the same time, due to The adhesion of halogen atoms can also improve the anti-slip performance of rubber shoes; then 3-fluoropropyltriethoxysilane will be hydrolyzed to generate silanol, and the silanol contained in the polyethylene glycol-polydimethylsiloxane block type long-chain hyperbranched copolymer can react with it to form a covalent bond, so that the polyethylene glycol-polydimethylsiloxane block type long-chain hyperbranched copolymer is grafted on the surface of the carbon fiber to obtain a modified carbon fiber. The modified carbon fiber has stable chemical properties and excellent The aging and corrosion resistance of the rubber base material is improved. During the vulcanization process of the rubber base material, the performance of the rubber base material is significantly affected. Through the protection of the silicon-oxygen chain segment, the performance of the modified carbon fiber is not weakened, but can improve the aging resistance, corrosion resistance and wear resistance of the rubber base material, thereby improving the wear resistance, corrosion resistance and aging resistance of the rubber shoe material and extending the service life of the rubber shoe material; and the polyethylene glycol-polydimethylsiloxane block type long-chain hyperbranched copolymer has a highly branched topological structure, which makes it have a small fluid mechanics volume, low viscosity, and contains a large number of terminal functional groups, such as silanol, hydroxyl, etc. Therefore, the modified carbon fiber grafted with polyethylene glycol-polydimethylsiloxane block type long-chain hyperbranched copolymer can be well connected with other compounds in the rubber base material, which not only increases the compatibility and interfacial bonding force between the carbon fiber and the rubber base material, but also increases the flexibility of the molecular chain of the rubber material and the free space of the rubber material when it is loaded, thereby improving the elasticity of the rubber shoe material. At the same time, the polyethylene glycol-polydimethylsiloxane block type long-chain hyperbranched copolymer has a highly branched topological structure and can also increase the chain entanglement between rubber molecules, thereby improving the mechanical properties of the rubber shoe material.
[0043] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0044] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.
Claims
1. A shoe material, characterized in that: The shoe material comprises the following raw materials in parts by weight: 15-25 parts of natural rubber, 30-45 parts of butadiene rubber, 18-24 parts of solution-polymerized styrene-butadiene rubber, 8-15 parts of modified inorganic filler, 5-8 parts of lubricant, 5-10 parts of antioxidant, 2-5 parts of plasticizer, 3.5-6 parts of vulcanization accelerator, 2-4 parts of antioxidant and 15-25 parts of modified carbon fiber.
2. A shoe material according to claim 1, characterized in that: The modified inorganic filler is modified white carbon black, and the preparation method of the modified white carbon black is as follows: (1) Dry the ground white carbon black in a vacuum drying oven at 140-150°C for 10-12 hours to obtain high-temperature activated white carbon black for later use; (2) adding the high temperature activated silica obtained in step (1) to the epichlorohydrin solvent, stirring and mixing evenly, then adding γ-aminopropyltrimethoxysilane, and ultrasonically dispersing at 120-150° C. for 2-4 hours to obtain γ-aminopropyltrimethoxysilane-grafted silica for standby use; wherein the mass ratio of silica to γ-aminopropyltrimethoxysilane is 1:(35-40); (3) dispersing molybdenum disulfide powder in water, adding dithiocarbyl alcohol thereto, and subjecting to ultrasonic reaction for 8-12 hours to obtain hydroxylated molybdenum disulfide for later use; wherein the mass ratio of molybdenum disulfide powder, water and dithiocarbyl alcohol is (0.45-0.6):(150-300):(2.5-8); (4) adding the γ-aminopropyltrimethoxysilane grafted silica obtained in step (2) to the hydroxylated molybdenum disulfide obtained in step (3), stirring at a speed of 800-900 r / min for 2-4 hours, filtering, washing, and drying to obtain modified silica; wherein the molar ratio of the γ-aminopropyltrimethoxysilane grafted silica to the hydroxylated molybdenum disulfide is (0.12-0.16):(0.03-0.05).
3. A shoe material according to claim 1, characterized in that: The preparation method of the modified carbon fiber specifically comprises the following steps: 1) Add the carbon fiber to a mixed acid solution of concentrated sulfuric acid and concentrated nitric acid, mix and react for 4-6 hours in an oil bath at 75-80°C, cool, rinse and dry the reaction product to obtain the pretreated carbon fiber for later use; 2) adding the pretreated carbon fiber obtained in step 1) to an ethanol solution of 3-fluoropropyltriethoxysilane, subjecting the mixture to ultrasonic oscillation, filtering and washing the reaction product to obtain carbon fiber grafted with 3-fluoropropyltriethoxysilane for standby use; the temperature of the ultrasonic oscillation is 50-60° C., the ultrasonic oscillation time is 8-10 h, and the ultrasonic oscillation power is 80-100 W; the mass percentage of 3-fluoropropyltriethoxysilane in the ethanol solution of 3-fluoropropyltriethoxysilane is 3-6%; the dosage ratio of the pretreated carbon fiber to the ethanol solution of 3-fluoropropyltriethoxysilane is 1 g:50-200 mL; 3) Under nitrogen protection, mix polyethylene glycol and terminal hydroxyl polydimethylsiloxane, and then raise the temperature. The method comprises the following steps: heating the mixture to 150-160° C., heating the mixture until the mixture is completely melted, adding hexamethylene diisocyanate after the mixture is melted, and stirring the mixture for reaction for 3-5 hours to obtain a polyethylene glycol-polydimethylsiloxane block type long chain hyperbranched copolymer for standby use; the mass ratio of the polyethylene glycol, the terminal hydroxyl polydimethylsiloxane and the hexamethylene diisocyanate is 1:(0.5-0.7):(1.5-1.8); the molecular weight of the polyethylene glycol is 1000-1200; the viscosity of the terminal hydroxyl polydimethylsiloxane is 800-1000 mm 2 / s; 4) adding the 3-fluoropropyltriethoxysilane grafted carbon fiber obtained in step 2) to the polyethylene glycol-polydimethylsiloxane block type long chain hyperbranched copolymer obtained in step 3), stirring the reaction at a speed of 400-600 r / min for 5-7 hours, and after the reaction, centrifuging, washing and drying the reaction product to obtain modified carbon fiber; the mass ratio of the 3-fluoropropyltriethoxysilane grafted carbon fiber to the polyethylene glycol-polydimethylsiloxane block type long chain hyperbranched copolymer is 1:(1.8-2.2).
4. A shoe material according to claim 1, characterized in that: The lubricant is any one or more of stearic acid, graphite and calcium carbonate.
5. A shoe material according to claim 1, characterized in that: The antioxidant is any one or more of antioxidant 1010, antioxidant 264 and antioxidant TNP.
6. A shoe material according to claim 1, characterized in that: The plasticizer is any one or more of methyl stearate, dioctyl phthalate and stearamide.
7. A shoe material according to claim 1, characterized in that: The vulcanization accelerator is any one or more of 4,4-dithiodimorpholine and 2-benzothiazolyl-N-morpholinyl sulfide.
8. A shoe material according to claim 1, characterized in that: The antioxidant is any one or more of antioxidant RD, antioxidant MB, antioxidant 4010, antioxidant 4010NA, and antioxidant 4020.
9. A method for preparing the shoe material according to any one of claims 1 to 8, characterized in that: The steps include: Step S1, mixing and stirring the lubricant, antioxidant and vulcanization accelerator to obtain a compounding agent for standby use; Step S2, mixing natural rubber, cis-1,4-butadiene rubber and solution polystyrene-butadiene rubber into an internal mixer for the first internal mixing, then adding part of the modified inorganic filler and continuing the second internal mixing, and when the temperature reaches 115-120° C., the rubber masterbatch is taken out from the internal mixer for standby use; Step S3, placing the rubber masterbatch obtained in step S2, the modified carbon fiber, the compounding agent obtained in step S1, the antioxidant, the plasticizer and the remaining modified inorganic filler into a rubber mixer for uniform mixing to obtain a mixed rubber for standby use; Step S4, placing the mixed rubber obtained in step S3 on a double-roll open mill for mixing for several times, adjusting the distance between the rollers to a desired thickness to obtain a film for standby use; Step S5, punching out shoe pieces of different shapes from the film obtained in step S4, wherein the shapes of the shoe pieces are designed according to different sole patterns, and the shoe pieces are placed in a matching mold for vulcanization to obtain the shoe material.
10. The method for preparing a shoe material according to claim 9, characterized in that: The first kneading time in step S2 is 8-15 minutes; the second kneading time is 6-8 minutes; the number of kneading in step S4 is 20-25 times; the vulcanization temperature of the shoe piece in the mold in step S5 is 150-160°C.
Citation Information
Patent Citations
Ice-surface oil-resistant non-slip shoe material and preparation method thereof
CN110317375A
Antiskid rubber sole and preparation method thereof
CN115368649A
Foamed rubber shoe material and method for preparing the same
US12054599B1
Leather scrap-modified rubber outsole and preparation method therefor
WO2022041930A1
Cited By
Silicone rubber anti-skid material for food shoes and preparation method of silicone rubber anti-skid material
CN122080646A